1990
DOI: 10.1002/1520-6807(199004)27:2<111::aid-pits2310270203>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the McCarthy scales

Abstract: The purpose of the present study was to test the factor structure of the McCarthy Scales of Children's Abilities in preschool children. Seventy-two boys and 69 girls between 4 and 5 years of age were tested. A factor analysis was carried out by means of the principal components method with varimax rotation. The existence of the Verbal factor and of the Perceptual-Performance factor was confirmed. The Quantitative and Memory factors appear undifferentiated. As far as the subtests which make up the Motor scale a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The Block Building subtest of the MSCA involves spatial organization and construction (Valencia, 1990) and visual-motor coordination (Kaufman & Kaufman, 1977). Factor analyses of McCarthy subtest scores of preschool-age children repeatedly have shown that Block Building loads on factors that correspond to McCarthy's original configuration of the Perceptual-Performance scale (Forns-Santacana & Gomez-Benito, 1990;Kaufman, 1975;Trueman, Lynch, & Branthwaite, 1984). According to Kaufman and Kaufman (1977), the Conceptual Grouping task involves logical classification skills and verbal reasoning ability; Counting and Sorting involves rote counting and is assumed to reflect ability in number concepts and numerical reasoning; and Number Questions involves number facts and concepts, numerical reasoning, computational skills, concentration, and verbal comprehension.…”
Section: Prenatal Testosterone and Specific Cognitive Abilitiesmentioning
confidence: 99%
“…The Block Building subtest of the MSCA involves spatial organization and construction (Valencia, 1990) and visual-motor coordination (Kaufman & Kaufman, 1977). Factor analyses of McCarthy subtest scores of preschool-age children repeatedly have shown that Block Building loads on factors that correspond to McCarthy's original configuration of the Perceptual-Performance scale (Forns-Santacana & Gomez-Benito, 1990;Kaufman, 1975;Trueman, Lynch, & Branthwaite, 1984). According to Kaufman and Kaufman (1977), the Conceptual Grouping task involves logical classification skills and verbal reasoning ability; Counting and Sorting involves rote counting and is assumed to reflect ability in number concepts and numerical reasoning; and Number Questions involves number facts and concepts, numerical reasoning, computational skills, concentration, and verbal comprehension.…”
Section: Prenatal Testosterone and Specific Cognitive Abilitiesmentioning
confidence: 99%
“…The goodness-of-fit of each scale was assessed with the following indexes: the Comparative Fit Index (CFI), the Root Mean Square Error of Approximation (RMSEA) and the Satorra-Bentler scaled chi-square difference test. Given that the factor structure has been found to vary between studies (Culbertson & Gyurke, 1990;Forns-Santacana & Gómez-Benito, 1990;Gómez-Benito & Forns-Santacana, 1993), we opted to assess the fit for each of the scales of the source instrument as well as for executive function scale. The long-term memory scale was not included in the CFA, given that it is based on two subtests of the original scale.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding previous versions of the MSCA, the scales show adequate internal consistency. Factor analyses carried out by different authors have shown that their structure is sensitive to sample characteristics, especially age and socio-economic level (Culbertson & Gyurke, 1990;Forns-Santacana & Gómez-Benito, 1990;Gómez-Benito, & Forns-Santacana, 1993). There is evidence of convergent validity both with scales for general developmental assessment and with tests to evaluate specific cognitive abilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For a detailed analysis of the base of support for the Popular Olympics, see Santacana (1990), particularly the chapter on the response of the athletic community.…”
mentioning
confidence: 99%